THE GREAT MIMICKER - TUBERCULOSIS - WMS, Farrah; N, Lavanya; Y, Yusniza (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Endocrinopathies have been reported to occur in patients with tuberculosis. METHODOLOGY We present 2 case reports illustrating pituitary gland tuberculosis in the immunocompromised i.e. in retroviral disease and in poorly controlled diabetes. RESULTS A 40-year-old man, with retroviral disease and smearpositive tuberculosis was referred for further evaluation of a 2 week-history of ataxic gait. History revealed that patient had erectile dysfunction and postural giddiness with double vision. Examination findings showed diplopia in all 4-gaze direction with no cerebellar signs. Cerebrospinal fluid analysis showed increased proteins with low/ normal glucose levels. Magnetic resonance imaging of the brain showed left fronto-temporal enhancing lesion with a suprasellar mass. Biochemical investigations suggest hypocortisolism and hypothyroidism. Patient was started on levothyroxine and hydrocortisone replacement therapy adjuvant to tuberculous meningitis treatment. Patient is currently 14 months into anti-tuberculous therapy, and resolution in the aspect of visual, neurological symptoms and radiological findings were seen. Repeated brain imaging showed resolution of white matter lesions and unchanged suprasellar mass. A 43-year-old lady, presented with hyperosmolar hyperglycemic syndrome (HHS) with acute delirium and agitation. Despite resolution of HHS, she constantly had altered mentation. Magnetic resonance imaging of the brain ensued and showed lobulated enhancing hypothalamic, both mammillary body, optic chiasm and pituitary stalk lesions suggestive of chronic granulomatous disease. Computed tomography of the thorax, abdomen and pelvis revealed consolidation over the upper lobe of the right lung warranting tuberculosis to be excluded. Further investigations showed that she also has concomitant hypocortisolism with hypothyroidism. Cerebrospinal fluid analysis showed normal glucose with elevated protein levels. She was diagnosed with tuberculoma complicated by hypopituitarism. Empiric tuberculosis treatment was started with the patient showing good response to therapy. CONCLUSION Physicians should be aware of extrapulmonary manifestations of tuberculosis, not uncommonly, the endocrinopathies.